KESETARAAN JENDER DALAM KEPUTUSAN BER KB DI PUSKESMAS KECAMATAN PALMERAH JAKARTA BARAT TAHUN 2022 - Safrudin, Safrudin; Suryati, Eros Siti; Rosidawati, Rosidawati (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2024)
Decision-making relatewith reproductive health is not fully in the hands of women sometimes it based on husband or family especially when problems with termination of pregnancy arise. This condition can lead women to death. The aim is to explore gender equality in family planning decisions were in Palmerah in West Jakarta District Health Center in 2009. The benefits of this research is to understand gender equality in family planning decisions were expected to prevent the occurrence of an unwanted pregnancy that led to the decline in maternal mortality. This research is quantitative descriptive design with cross sectional correlation. By involving 131 mothers as the respondent. Data were analyzed by univariate, bivariate and multivariate. Results showed gender equality in family planning decisions were the most are those that have gender equality in family planning decisions were numbered 68 women (51.9%) and independent variables that have significant knowledge (p = 0.000), P-value attitudes (p = 0.000) P-value perception (p = 0.000) and for the characteristics of the mother and the father of P-value for Age Mr (p = 0049), P-value for Mother Works (p = 0.000), P-value for family income (p = 0021). Statistical tests can be performed because of logistic regression analysis results bivariatnya to determine the candidates all have the value p value <0.25. Of the six variables are independent variables age of the father of the P-Wald 0.016 most related to gender equality in family planning decisions were once controlled by the Income Families P-Wald 0.025. The results of this study recommends to the Head of Puskesmas Kec. Palmerah to improve the promotion of gender equality. Recommendations are also given to other researchers who intend to conduct research on gender equality to involve more variables that were assessed with different design and use instruments that have validity and reliability of raw value.